Evaluation of pulmonary nodules in Asian population - Phua, Chee K.; Sim, Wen Y.; Tee, Kuan Sen; Lew, Sennen J. W.; Lim, Albert Y. H.; Tai, Dessmon Y. H.; Goh, Soon Keng; Kor, Ai Ching; Ng, Alan W. K.; Abisheganaden, John; Verma, Akash (Journal of Thoracic Disease; Vol 8, No 5 (May 01, 2016): Journal of Thoracic Disease, 2016)
Background: American College of Chest Physicians (ACCP) provides guidelines to manage pulmonary nodules. Pulmonary nodules however can be malignant or benign. Similar incidence of tuberculosis (TB) and lung cancer in Asian countries raises concern over the relevance of suggested guidelines in Asian population. There is little data on the pattern of clinical practice in the management of pulmonary nodules in Asian country (Singapore). Our study describes the current pattern of clinical practice in this area highlighting the variation in practice and discussing the potential reasons. Methods: Retrospective review of the medical records of patients diagnosed with lung cancer in 2010. Results: Sixty nodules were identified in 32 patients. Nodules were detected incidentally on routine imaging in 7 (21.9%) patients. TB contact tracing and pre-employment screening were common ways by which nodules were detected incidentally. Over one third (37.5%) were non-smokers. Majority of nodules were located in the upper lobes of right and left lung followed by right lower lobe (RLL). Only few patients 8 (25%) had positron emission tomography (PET) scan for staging purposes. There were no difference in survival between patients who presented with single, 747 (range, 25–1,840) days vs. multiple nodules 928 (range, 30–2,572) days, P=0.26. In a retrospective analysis of malignancy risk with the probability calculator, 62.5% patients were at low-moderate risk whilst 32.5% were at high risk. Conclusions: The clinical practice of managing pulmonary nodules in Asian population differs from ACCP guidelines. None of the patient had pre-test probability calculated, and few had PET scan. This is because upper lobe predominance of lung cancer is identical to TB, non-smoking history does not have any weight in discounting malignancy risk where many of the Asian lung cancer patients are non-smokers, and the local endemicity of TB and its confounding effect on radiological findings of CT scan and PET scan.